Self-repairing organic-inorganic composite electrolyte membrane and application thereof

By using a self-healing organic and inorganic composite electrolyte membrane with multi-stage hydrogen bonds in all-solid lithium metal batteries, the problem of aging of lithium dendrites and electrolyte membranes is solved, and the battery life and rate performance is improved.

CN119823636APending Publication Date: 2025-04-15WEICHAI POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510042606.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The formation and growth of lithium dendrites in all-solid lithium metal batteries affect the battery life and magnification, and commonly used polymer binders age at high temperatures, resulting in the electrolyte membrane becoming brittle, resulting in dry cracks, and inability to repair itself.

Method used

The self-healing organic inorganic composite electrolyte membrane with a physical crosslinked structure using a multi-stage hydrogen bond forms a polyurethane urea elastomer material through prepolymerization of PCL-OH with phenone diisocyanate and tin-based catalyst, with a reversible hydrogen bond array, which can repair cracks under heating stimulation.

Benefits of technology

It improves the strength and toughness of the electrolyte membrane, realizes self-repair of cracks, extends the battery life and improves the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237395760000081
    Figure BDA0005237395760000081
  • Figure HDA0005237395770000011
    Figure HDA0005237395770000011
  • Figure HDA0005237395770000012
    Figure HDA0005237395770000012
Patent Text Reader

Abstract

The invention provides a self-repairing organic-inorganic composite electrolyte membrane and application thereof. The preparation method comprises the following steps: heating PCL-OH to 60-120 DEG C in a nitrogen atmosphere, vacuumizing, adding phorone diisocyanate and a tin-based catalyst, and carrying out a prepolymerization reaction; mixing and stirring the obtained prepolymer and an ester solvent; adding a chain extender into the obtained uniform solution for reaction; mixing the obtained polyurethane urea elastomer solution with the viscosity of 100 to 2000mPa. S, ionic liquid and electrolyte powder, and stirring to obtain composite slurry; and coating and drying the composite slurry to obtain the composite electrolyte membrane. According to the preparation method, amido urea and carbamate groups are introduced into polyurethane-urea with polycaprolactone as a main chain, multiple hydrogen bonds can be formed between the amido urea and carbamate, and the multiple hydrogen bonds are gathered into a multistage hydrogen bond array; crosslinking the amorphous PCL soft segment by the hydrogen bond array; due to reversibility of the hydrogen bond array, the electrolyte membrane with cracks can be repaired under heating stimulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrolyte membranes, and in particular relates to a self-repairing organic-inorganic composite electrolyte membrane and applications thereof. Background Art

[0002] The key issue affecting the lifespan and rate capability of all-solid-state lithium metal batteries is the formation and growth of lithium dendrites.

[0003] Commonly used polymer binders are prone to aging at higher temperatures, causing the electrolyte membrane to become brittle and produce dry cracks. Secondly, the electrolyte membrane cannot avoid cracks caused by the lithium deposition and stripping process. Once cracks are generated, they cannot be restored. These cracks are the main cause of lithium dendrite growth in solid electrolytes. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a self-healing organic-inorganic composite electrolyte membrane and its application. The composite electrolyte membrane has a physical cross-linked structure of multi-level hydrogen bonds. Due to the reversibility of the multi-level hydrogen bonding effect, the cracked electrolyte membrane can be repaired under heating stimulation.

[0005] The present invention provides a self-repairing organic-inorganic composite electrolyte membrane, which is prepared according to the following method:

[0006] The PCL-OH is heated to 60-120° C. in a nitrogen atmosphere, and then vacuumized, and then isophorone diisocyanate and a tin-based catalyst are added to perform a prepolymerization reaction to obtain a prepolymer;

[0007] The prepolymer and the solvent are mixed and stirred to obtain a uniform solution;

[0008] Adding a chain extender to the uniform solution to react and obtain a polyurethane urea elastomer solution having a viscosity of 100 to 2000 mPa.s;

[0009] The polyurethane urea elastomer solution, the ionic liquid and the electrolyte powder are mixed and stirred to obtain a composite slurry;

[0010] The composite slurry is coated and dried to obtain a self-repairing organic-inorganic composite electrolyte membrane.

[0011] Preferably, the molar ratio of PCL-OH to isophorone diisocyanate is (1:1) to (1:4);

[0012] The tin-based catalyst accounts for 0.5 to 3 wt % in the prepolymerization system.

[0013] Preferably, the solvent is selected from one or more of dimethyl carbonate, ethyl acetate, amyl acetate, butyl butyrate, hexyl butyrate, tetrahydrofuran, and p-xylene.

[0014] Preferably, the prepolymerization temperature is 75 to 85° C., and the prepolymerization time is 1 to 5 hours.

[0015] Preferably, the chain extender is a dihydroxy-terminated chain extender of 2-ureido-4-pyrimidone unit and / or isophthalic acid hydrazide; the temperature for adding the chain extender to react is 10 to 30° C. and the reaction time is 22 to 26 hours.

[0016] Preferably, the ionic liquid is selected from one or more of 1-ethyl-3-methylimidazolium nitrate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylphosphate and 1-ethylpyridinium bistrifluoromethanesulfonyl imide salt;

[0017] The electrolyte powder is selected from one or more of a sulfide electrolyte, an oxide electrolyte and a halide electrolyte.

[0018] Preferably, the sulfide electrolyte is selected from Li6PS5Cl, Li 5.5 PS5Cl 1.5 、Li7P3S 11 and Li 10 GeP2S 12 One or more of;

[0019] The oxide electrolyte is selected from one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO) and lithium aluminum titanium phosphate (LATP);

[0020] The halide electrolyte is selected from Li3InCl6 or Li4YI7.

[0021] Preferably, the thickness of the self-repairing organic-inorganic composite electrolyte membrane is 20 to 80 μm.

[0022] The present invention provides a solid-state lithium battery, comprising a positive electrode sheet and a composite negative electrode sheet;

[0023] The composite negative electrode sheet is prepared according to the following method:

[0024] The composite slurry described in the above technical solution is scraped onto one side of the silver-carbon negative electrode sheet and dried to obtain a composite negative electrode sheet with a thickness of 20 to 80 μm.

[0025] The composite slurry layer of the composite negative electrode sheet and the positive electrode sheet are laminated, subjected to warm isostatic pressing, and packaged to obtain a lithium-ion battery.

[0026] Preferably, the pressure of the warm isostatic pressing treatment is 300-600 MPa, the temperature of the warm isostatic pressing treatment is 60-120° C., and the time of the warm isostatic pressing treatment is 10-30 min.

[0027] The invention provides a self-repairing organic-inorganic composite electrolyte membrane, which is prepared according to the following method: heating PCL-OH to 60-120°C in a nitrogen atmosphere, evacuating, and then adding phorone diisocyanate and a tin-based catalyst to perform a prepolymerization reaction to obtain a prepolymer; mixing the prepolymer with an ester solvent, stirring, and obtaining a uniform solution; adding a chain extender to the uniform solution to react, and obtaining a polyurethane urea elastomer solution with a viscosity of 100-2000 mPa.s; mixing the polyurethane urea elastomer solution with an ionic liquid and an electrolyte powder, stirring, and obtaining a composite slurry; coating and drying the composite slurry to obtain a self-repairing organic-inorganic composite electrolyte membrane. In the present invention, under the action of a tin-based catalyst, PCL-OH and an isocyanate group (-NCO) in a diisocyanate undergo an addition reaction to form a diisocyanate containing polyester and polyether in the middle; a dihydroxyl group (-OH) of a chain extender reacts with isocyanate groups (-NCO) at both ends of a prepolymer to generate a carbamate bond; an amide urea bond is a functional group of the chain extender itself; amide urea and carbamate groups are introduced into a polyurethane-urea (PUU) having polycaprolactone (PCL) as a main chain, multiple hydrogen bonds can be formed between the amide urea and the carbamate, and the amide urea and the carbamate are aggregated into a multi-level hydrogen bond array; the hydrogen bond array cross-links an amorphous PCL soft segment to form a high-performance polyurethane urea elastomer material; and due to the reversibility of the hydrogen bond array in the polyurethane urea elastomer material, an electrolyte membrane with cracks can be repaired under heating stimulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The groups contained in the self-repairing organic-inorganic composite electrolyte membrane provided by the present invention;

[0029] Figure 2 A schematic diagram of the self-repairing of the self-repairing organic-inorganic composite electrolyte membrane provided by the present invention. DETAILED DESCRIPTION

[0030] The present invention provides a self-repairing organic-inorganic composite electrolyte membrane, which is prepared by the following method:

[0031] The PCL-OH is heated to 60-120° C. in a nitrogen atmosphere, and then vacuumized, and then phorone diisocyanate (IPDI) and a tin-based catalyst are added to perform a prepolymerization reaction to obtain a prepolymer;

[0032] The prepolymer and the ester solvent are mixed and stirred to obtain a uniform solution;

[0033] Adding a chain extender to the uniform solution to react and obtain a polyurethane urea elastomer solution having a viscosity of 100 to 2000 mPa.s;

[0034] The polyurethane urea elastomer solution, the ionic liquid and the electrolyte powder are mixed and stirred to obtain a composite slurry;

[0035] The composite slurry is coated and dried to obtain a self-repairing organic-inorganic composite electrolyte membrane.

[0036] In the present invention, under the action of a tin-based catalyst, PCL-OH and the isocyanate group (-NCO) in the diisocyanate undergo an addition reaction to form a diisocyanate containing polyester and polyether in the middle; the dihydroxyl (-OH) of the chain extender reacts with the isocyanate groups (-NCO) at both ends of the prepolymer to form a carbamate bond; the amidourea bond is the functional group of the chain extender itself. In the present invention, amidourea and carbamate groups are introduced into a polyurethane-urea (PUU) with polycaprolactone (PCL) as the main chain, and multiple hydrogen bonds can be formed between amidourea and carbamate, which aggregate into a multi-level hydrogen bond array; the hydrogen bond array cross-links the amorphous PCL soft segment to form a high-performance polyurethane urea elastomer material; due to the reversibility of the hydrogen bond array in the polyurethane urea elastomer material, the cracked electrolyte membrane can be repaired under heating stimulation.

[0037] The present invention heats PCL-OH to 60-120° C. under a nitrogen atmosphere, evacuates, and then adds phorone diisocyanate and a tin-based catalyst for prepolymerization to obtain a prepolymer. The molar ratio of PCL-OH to phorone diisocyanate in the present invention is (1:1) to (1:4); the tin-based catalyst accounts for 0.5-3wt% in the prepolymerization system; in a specific embodiment, the tin-based catalyst is dibutyltin dilaurate (DBTDL); the molar ratio of PCL-OH to phorone diisocyanate is 1:1.2, and dibutyltin dilaurate accounts for 0.5wt% in the prepolymerization system.

[0038] The present invention heats PCL-OH to 80-100° C. under a nitrogen atmosphere and evacuates to remove moisture and oxygen. The present invention evacuates to remove moisture and oxygen. The temperature of the prepolymerization reaction is 75-85° C., and the time of the prepolymerization reaction is 1-5 hours. In a specific embodiment, the temperature of the prepolymerization reaction is 80° C., and the time is 2 hours.

[0039] After obtaining the prepolymer, the present invention mixes the prepolymer and an ester solvent, stirs, and obtains a uniform solution. The ester solvent in the present invention is selected from one or more of dimethyl carbonate, ethyl acetate, amyl acetate, butyl butyrate, and hexyl butyrate. The mass ratio of the ester solvent to the prepolymer in the present invention is (2:0.5) to (2:1).

[0040] After obtaining a uniform solution, the present invention adds a chain extender to the uniform solution to react and obtain a polyurethane urea elastomer solution with a viscosity of 100 to 2000 mPa.s. The chain extender used in the present invention is a dihydroxy-terminated chain extender and / or isophthalic acid hydrazide of a 2-ureido-4-pyrimidone unit; they are all commercially available products; the temperature for adding the chain extender to react is room temperature, preferably 10 to 30°C, and the time is 22 to 26 hours. The molecular weight of the polyurethane urea elastomer is 1000 to 500000. The viscosity of the polyurethane urea elastomer solution is 100 to 2000 mPa.s, preferably 1000 to 2000 mPa.s.

[0041] After obtaining the polyurethane urea elastomer solution, the present invention mixes the polyurethane urea elastomer solution with an ionic liquid and an electrolyte powder, and stirs to obtain a composite slurry. The ionic liquid in the present invention is selected from one or more of 1-ethyl-3-methylimidazolium nitrate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylphosphate and 1-ethylpyridine bistrifluoromethanesulfonyl imide salt; the electrolyte powder is selected from one or more of sulfide electrolytes, oxide electrolytes and halide electrolytes. The sulfide electrolyte in the present invention is selected from Li6PS5Cl, Li 5.5 PS5Cl 1.5 、Li7P3S 11 and Li 10 GeP2S 12 The oxide electrolyte is selected from one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO) and lithium aluminum titanium phosphate (LATP); the halide electrolyte is selected from Li3InCl6 and / or Li4YI7. In a specific embodiment, the electrolyte powder is selected from Li6PS5Cl or lithium lanthanum zirconium tantalum oxide (LLZTO) electrolyte powder.

[0042] The mass ratio of the polyurethane urea elastomer solution, the ionic liquid and the electrolyte powder in the present invention is (2:0.5:97.5) to (10:5:85).

[0043] The thickness of the self-repairing organic-inorganic composite electrolyte membrane provided by the invention is 20-80 μm.

[0044] The self-repairing organic-inorganic composite electrolyte membrane provided by the present invention includes ureido-pyridone-group, urea-group and carbamate-group, such as Figure 1 shown.

[0045] The present invention also provides a solid-state lithium battery, comprising a positive electrode sheet and a composite negative electrode sheet;

[0046] The composite negative electrode sheet is prepared according to the following method:

[0047] The composite slurry in the above technical solution is scraped onto one side of the silver-carbon negative electrode sheet and dried to obtain a composite negative electrode sheet;

[0048] The composite slurry layer of the composite negative electrode sheet and the positive electrode sheet are laminated, subjected to warm isostatic pressing, and packaged to obtain a lithium-ion battery.

[0049] The positive electrode sheet in the present invention is made according to NCM811:Li 5.5 PS5Cl 1.5 : vapor grown carbon fiber (VGCF) = 80:17:3 (mass ratio) are mixed evenly to obtain powder; then slurry is prepared according to the ratio of powder: binder = 97:3 (mass ratio), the binder is selected from one or more of PIB, SBR and SEBE, and the solvent is selected from p-xylene; the solid content is 40%; the current collector of the positive electrode sheet is aluminum foil; the thickness of the coating on the positive electrode sheet is 50 to 120 μm.

[0050] The thickness of the silver-carbon negative electrode sheet used in the present invention is 3-5 μm; the thickness of the composite silver-carbon negative electrode is 30-80 μm;

[0051] In the present invention, the drying temperature is 75-85° C. and the drying time is 10-14 h; in a specific embodiment, the drying temperature is 80° C. and the drying time is 12 h.

[0052] The present invention uses a die-cutting machine to cut the composite negative electrode sheet and the positive electrode sheet; after the composite slurry layer of the cut composite negative electrode sheet is attached to the positive electrode sheet, a warm isostatic pressing treatment is performed, and packaging is performed to obtain a solid-state battery.

[0053] The pressure of the warm isostatic pressing treatment in the present invention is 300-600 MPa, the temperature of the warm isostatic pressing treatment is 60-120°C, and the time of the warm isostatic pressing treatment is 10-30 min. In a specific embodiment, the pressure of the warm isostatic pressing treatment is 300 MPa, the temperature is 80°C, and the time is 10 min. After the warm isostatic pressing treatment, a self-repairing organic-inorganic composite electrolyte membrane is formed between the positive electrode sheet and the silver carbon.

[0054] The repair temperature of the composite electrolyte membrane provided by the present invention is 25 to 80°C. The repair schematic diagram is as follows: Figure 2 shown.

[0055] The composite electrolyte membrane in the lithium ion battery provided by the present invention has a physical cross-linked structure of multi-level hydrogen bonds. Due to the reversibility of the multi-level hydrogen bonds, the repair ability of the electrolyte membrane is improved; the polyurethane urea elastomer is used as the binder of the composite electrolyte membrane. Due to the presence of hydrogen bonds, the strength and toughness of the composite electrolyte membrane are improved; the ionic liquid added in the preparation process promotes the transport of lithium ions to a certain extent.

[0056] The organic-inorganic composite electrolyte membrane of the present invention can perform self-repairing during the warm isostatic pressing process and the subsequent post-packaging test process; the self-repairing temperature is 25-80°C.

[0057] In order to further illustrate the present invention, a self-repairing organic-inorganic composite electrolyte membrane and its application provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0058] Comparative Example

[0059] Prepare 5% SBR-paraxylene glue, prepare electrolyte powder: SBR into slurry in a ratio of 98:2, with a solid content of 45%. After stirring with a vacuum degassing machine for a period of time, apply it on the silver-carbon negative electrode, dry it naturally, and blow dry it at 80°C for 10 hours to obtain a 100-micron-thick composite silver-carbon electrode. The treated ternary nickel-cobalt-manganese 811 positive electrode and composite silver-carbon negative electrode are cut using a die-cutting machine. The obtained positive electrode / electrolyte membrane / composite negative electrode are bonded, and sulfuric acid paper and PET are used as buffer layers on both sides, and then warm isostatic pressing is performed at a pressure of 500MPa. The obtained pole piece is packaged and tested, and the test conditions are 2.5V-4.25V. Using this method, obvious cracks and gaps will appear in the lithium deposition and stripping process.

[0060] Example 1

[0061] PCL-OH was heated to about 80°C in a nitrogen atmosphere, and vacuum was applied to remove moisture and oxygen. Then, phorone diisocyanate (IPDI) and dibutyltin dilaurate (DBTDL) were added, and stirred at 80°C for 2 hours to obtain a prepolymer, wherein the molar ratio of PCL-OH:IPDI was 1:1.2; and the content of dibutyltin dilaurate in the system was 0.5%.

[0062] 2. Add 2 g of ethyl acetate solvent to 1 g of the above prepolymer and stir to obtain a uniform solution; then add chain extender isophthalic acid hydrazide (IPDH) and react at room temperature for 24 hours to obtain a polyurethane urea elastomer solution of 1000 mPa.s.

[0063] 3. Add 0.5 mol / L 1-ethyl-3-methylimidazole nitrate and 2 g Li6PS5Cl electrolyte powder to the polyurethane urea solution in step 2, stir at 500 rpm for 1 hour at room temperature to obtain a composite slurry. Then, apply the composite slurry to a 5 μm thick silver-carbon negative electrode with a scraper thickness of 200 μm, and dry at 80 ° C for 12 hours to obtain a composite negative electrode sheet. The thickness of the self-repairing organic-inorganic composite electrolyte membrane in the composite negative electrode sheet is 30 μm.

[0064] 4.According to NCM811:Li 5.5 PS5Cl1.5 : vapor grown carbon fiber (VGCF) = 80:17:3 (mass ratio) are mixed evenly to obtain powder; then slurry is prepared according to the ratio of powder: binder = 97:3 (mass ratio), the binder is selected from SBR, and the solvent is selected from paraxylene; the solid content is 40%; the slurry is coated on Al foil, the coating scraper thickness is 450μm, and the drying and baking thickness is 100μm.

[0065] The composite negative electrode sheet obtained in step 3 and the pre-treated positive electrode sheet are cut using a die-cutting machine, wherein the size of the positive electrode sheet is 2.5 cm×3 cm and the size of the composite negative electrode sheet is 2.8 cm×3.2 cm;

[0066] 5: The composite negative electrode sheet and the positive electrode sheet obtained in step 4 are laminated, and then warm isostatic pressing is performed using a pressure of 300 MPa; the processing temperature is 80° C. and the time is 10 min.

[0067] 6: The soft-pack battery obtained in step 5 is spot welded, packaged and tested, with a test range of 2.5 to 4.2V.

[0068] Example 2

[0069] 1. Heat PCL-OH to about 80°C in a nitrogen atmosphere, and evacuate to remove moisture and oxygen. Then add phorone diisocyanate (IPDI) and dibutyltin dilaurate (DBTDL), and stir at 80°C for 2h to obtain a prepolymer, wherein the molar ratio of PCL-OH:IPDI is 1:1.2; the content of dibutyltin dilaurate in the system is 0.5%.

[0070] 2. Add 2 g of dimethyl carbonate solvent to 1 g of the above prepolymer and stir to obtain a uniform solution; then add chain extender isophthalic acid hydrazide (IPDH) and react at room temperature for 24 hours to obtain a polyurethane urea elastomer solution of 2000 mPa.s.

[0071] 3. Add 0.5 mol / L 1-ethyl-3-methylimidazole nitrate and 2 g LLZTO electrolyte powder to the polyurethane urea solution in step 2, and stir at 1000 rpm for 1 hour at room temperature to obtain a composite slurry. Then, the composite slurry is scraped onto a 5 μm thick silver-carbon negative electrode with a scraper thickness of 200 μm, and dried at 80 ° C for 12 hours to obtain a composite negative electrode sheet. The thickness of the self-repairing organic-inorganic composite electrolyte membrane in the composite negative electrode sheet is 30 μm.

[0072] 4.According to NCM811:Li 5.5 PS5Cl 1.5: vapor grown carbon fiber (VGCF) = 80:17:3 (mass ratio) are mixed evenly to obtain powder; then slurry is prepared according to the ratio of powder: binder = 97:3 (mass ratio), the binder is selected from PIB, and the solvent is selected from p-xylene; the solid content is 40%; the slurry is coated on Al foil, the coating scraper thickness is 450μm, and the drying and baking thickness is 100μm.

[0073] The composite negative electrode sheet obtained in step 3 and the pre-treated positive electrode sheet are cut using a die-cutting machine, wherein the positive electrode sheet has a size of 2.5 cm×3 cm and the composite negative electrode sheet has a size of 2.8 cm×3.2 cm;

[0074] 5. The composite negative electrode sheet and the positive electrode sheet obtained in step 4 are laminated, and then warm isostatic pressing is performed using a pressure of 300 MPa; the processing temperature is 80° C. and the time is 10 min.

[0075] 6. Perform electric welding, packaging and testing on the soft pack battery obtained in step 5, with the test range of 2.5-4.2V.

[0076] Example 3

[0077] 1. Heat PCL-OH to about 80°C in a nitrogen atmosphere, and evacuate to remove moisture and oxygen. Then add phorone diisocyanate (IPDI) and dibutyltin dilaurate (DBTDL), and stir at 80°C for 2h to obtain a prepolymer, wherein the molar ratio of PCL-OH:IPDI is 1:1.5; the content of dibutyltin dilaurate in the system is 1%.

[0078] 2. Add 2 g of ethyl acetate solvent to 1 g of the above prepolymer and stir to obtain a uniform solution; then add a dihydroxy-terminated chain extender of 2-ureido-4-pyrimidone unit and react at room temperature for 24 hours to obtain a polyurethane urea elastomer solution of 1500 mPa.s.

[0079] 3. Add 0.5 mol / L 1-ethyl-3-methylimidazole nitrate and 2 g LLZTO electrolyte powder to the polyurethane urea solution in step 2, and stir at 1000 rpm for 1 hour at room temperature to obtain a composite slurry. Then, the composite slurry is scraped onto a 5 μm thick silver-carbon negative electrode with a scraper thickness of 200 μm, and dried at 80 ° C for 12 hours to obtain a composite negative electrode sheet. The thickness of the self-repairing organic-inorganic composite electrolyte membrane in the composite negative electrode sheet is 40 μm.

[0080] 4.According to NCM811:Li 5.5 PS5Cl 1.5: vapor grown carbon fiber (VGCF) = 80:17:3 (mass ratio) are mixed evenly to obtain powder; then slurry is prepared according to the ratio of powder: binder = 97:3 (mass ratio), the binder is selected from PIB, and the solvent is selected from p-xylene; the solid content is 40%; the slurry is coated on Al foil, the coating scraper thickness is 450μm, and the drying and baking thickness is 100μm.

[0081] The composite negative electrode sheet obtained in step 3 and the pre-treated positive electrode sheet are cut using a die-cutting machine, wherein the size of the positive electrode sheet is 2.5 cm×3 cm and the size of the composite negative electrode sheet is 2.8 cm×3.2 cm;

[0082] 5. The composite negative electrode sheet and the positive electrode sheet obtained in step 4 are laminated, and then warm isostatic pressing is performed using a pressure of 300 MPa; the processing temperature is 80° C. and the time is 10 min.

[0083] 6. Perform electric welding and packaging on the soft-pack battery obtained in step 5.

[0084] 7. The negative electrode-free lithium metal battery was tested with a voltage range of 2.5-4.2V and a test temperature of 55°C.

[0085] The present invention performs performance tests on the batteries prepared in Examples 1 to 3, and the results are shown in Table 1:

[0086] Table 1

[0087]

[0088]

[0089] After comparative analysis, the 0.2C charge and discharge specific capacities of the soft-packed cells assembled with unrepaired electrolytes were 155.2mAh / g and 130.1mAh / g, respectively, with an initial efficiency of 83.87%, and a rapid capacity decay after 100 cycles. The capacity of the repaired electrolyte membrane has been improved, and the initial efficiency has been improved, which indirectly indicates that the dry cracks of the electrolyte membrane itself have been reduced, and the gaps and cracks generated during the cycle are repaired at a temperature of 55°C, thereby improving the density of the electrolyte membrane, improving the performance of the cell, and thus improving the performance of the battery.

[0090] It can be seen from the above embodiments that the present invention provides a self-healing organic-inorganic composite electrolyte membrane, which is prepared according to the following method: heating PCL-OH to 60-120°C under a nitrogen atmosphere, evacuating, and then adding phorone diisocyanate and a tin-based catalyst to perform a prepolymerization reaction to obtain a prepolymer; mixing the prepolymer and an ester solvent, stirring to obtain a uniform solution; adding a chain extender to the uniform solution to react to obtain a polyurethane urea elastomer solution with a viscosity of 100-2000 mPa.s; mixing the polyurethane urea elastomer solution with an ionic liquid and an electrolyte powder, stirring to obtain a composite slurry; coating and drying the composite slurry to obtain a self-healing organic-inorganic composite electrolyte membrane. In the present invention, under the action of a tin-based catalyst, PCL-OH and an isocyanate group (-NCO) in a diisocyanate undergo an addition reaction to form a diisocyanate containing polyester and polyether in the middle; a dihydroxyl group (-OH) of a chain extender reacts with isocyanate groups (-NCO) at both ends of a prepolymer to generate a carbamate bond; an amide urea bond is a functional group of the chain extender itself; amide urea and carbamate groups are introduced into a polyurethane-urea (PUU) having polycaprolactone (PCL) as a main chain, multiple hydrogen bonds can be formed between the amide urea and the carbamate, and the amide urea and the carbamate are aggregated into a multi-level hydrogen bond array; the hydrogen bond array cross-links an amorphous PCL soft segment to form a high-performance polyurethane urea elastomer material; and due to the reversibility of the hydrogen bond array in the polyurethane urea elastomer material, an electrolyte membrane with cracks can be repaired under heating stimulation. The experimental results show that the charge specific capacity at 0.2C is 158.3~160.2mAh / g, the discharge specific capacity is 139.8~142.5mAh / g, the first efficiency is 88.3~89.4%, and the 100-cycle capacity retention rate is 63~70%.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A self-repairing organic-inorganic composite electrolyte membrane, characterized in that: Prepared according to the following method: The PCL-OH is heated to 60-120° C. in a nitrogen atmosphere, and then vacuumized, and then phorone diisocyanate and a tin-based catalyst are added to perform a prepolymerization reaction to obtain a prepolymer; The prepolymer and the ester solvent are mixed and stirred to obtain a uniform solution; a chain extender is added to the uniform solution to react to obtain a polyurethane urea elastomer solution with a viscosity of 100 to 2000 mPa.s; The polyurethane urea elastomer solution, the ionic liquid and the electrolyte powder are mixed and stirred to obtain a composite slurry; The composite slurry is coated and dried to obtain a self-repairing organic-inorganic composite electrolyte membrane.

2. The self-repairing organic-inorganic composite electrolyte membrane according to claim 1, characterized in that: The molar ratio of PCL-OH to phorone diisocyanate is (1:1) to (1:4); The tin-based catalyst accounts for 0.5 to 3 wt % in the prepolymerization system.

3. The self-repairing organic-inorganic composite electrolyte membrane according to claim 1, characterized in that: The ester solvent is selected from one or more of dimethyl carbonate, ethyl acetate, amyl acetate, butyl butyrate and hexyl butyrate.

4. The self-repairing organic-inorganic composite electrolyte membrane according to claim 1, characterized in that: The temperature of the prepolymerization reaction is 75-85° C., and the time of the prepolymerization reaction is 1-5 hours.

5. The self-repairing organic-inorganic composite electrolyte membrane according to claim 1, characterized in that: The chain extender is a dihydroxy-terminated chain extender of 2-ureido-4-pyrimidone units and / or isophthalic acid hydrazide; The reaction temperature of adding the chain extender is 10-30°C and the reaction time is 22-26 hours.

6. The self-repairing organic-inorganic composite electrolyte membrane according to claim 1, characterized in that: The ionic liquid is selected from one or more of 1-ethyl-3-methylimidazolium nitrate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylphosphate and 1-ethylpyridine bistrifluoromethanesulfonyl imide; The electrolyte powder is selected from one or more of a sulfide electrolyte, an oxide electrolyte and a halide electrolyte.

7. The self-repairing organic-inorganic composite electrolyte membrane according to claim 6, characterized in that: The sulfide electrolyte is selected from Li6PS5Cl, Li 5.5 PS5Cl 1.5 、Li7P3S 11 and Li 10 GeP2S 12 One or more of; The oxide electrolyte is selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide and lithium aluminum titanium phosphate; The halide electrolyte is selected from Li3InCl6 and / or Li4YI7.

8. The self-repairing organic-inorganic composite electrolyte membrane according to claim 1, characterized in that: The thickness of the self-repairing organic-inorganic composite electrolyte membrane is 20 to 80 μm.

9. A solid-state lithium battery, characterized in that: Including positive electrode sheet and composite negative electrode sheet; The composite negative electrode sheet is prepared according to the following method: Scrape the composite slurry described in claim 1 onto one side of the silver-carbon negative electrode sheet, and dry it to obtain a composite negative electrode sheet; The composite slurry layer of the composite negative electrode sheet and the positive electrode sheet are laminated, subjected to warm isostatic pressing, and packaged to obtain a lithium-ion battery.

10. The lithium ion battery according to claim 1, characterized in that: The pressure of the warm isostatic pressing treatment is 300-600 MPa, the temperature of the warm isostatic pressing treatment is 60-120° C., and the time of the warm isostatic pressing treatment is 10-30 min.